MODELING OF VEHICLE TYRES DEPENDING ON THE DEGREE OF CHANGE OF EXTERNAL FACTORS - Abdulatif Meliboyev (Western European Studies, 2024)
In the article economic efficiency monitoring system constant respectively to the driver and technical to the service of tyres real pressure about the message to give depends Accordingly, it is known one in time real the pressure to know tyres pressure condition for average from the indicator exclusion significant level reduces These are the tyres life from loss and of pressure change with depends fuel excess from spending keep shown
Keywords: Legality; value; pressure